5S implementation methodologies: literature review and directions. (2017) - Randhawa, Jugraj Singh; Ahuja, Inderpreet Singh
The objective of the paper is to investigate the process of 5S implementation across all the levels of organisations and highlight the significant contributions of 5S to the organisations. The paper is based on a methodical literature review that inspects how the implementation of 5S technique significantly contributed the progress of different organisations in the term of quality, productivity, effective utilisation of space, safety and employees morale values. The manuscript presents the systematic 5S implementation initiatives implementation methodologies suggested by various researchers and practitioners. The success factors that enrich 5S implementation in the organisation are also identified and discussed progressively. The study also highlights the manufacturing achievements through successful 5S initiatives and obstacles that create hindrance in the path of implementing 5S technique. The paper provides comprehensive outlook of 5S approach to the management for implementing it as way of attaining maintainable performance for their organisations.